Introducing a Multimodal Framework in English Language Reading Assessment - Chan, Caroline; Choo, Suzanne (INTI University College, 2009)
The Visual Arts, once a distinct discipline on its own, has now been infused in almost all aspects of 21” century culture so that modern society is often described as ‘media-saturated’ and its citizens commonly termed ‘technological natives’ (Freedman, 2003). Within this context, two observations may be made concerning the notion of the ‘text’. The first is that whereas writing was the dominant mode of communication a few centuries ago, this has now been replaced by the dominance of the image (Kress. 2003; Kress and Van Leeuwen, 2006). In an examination of learning materials in schools such as text-books, web-resources and teacher-produced materials, Kress and Bezemer (2008) note that images have overtaken writing as the primary carriers of meaning. In science and mathematics textbooks for example, illustration arid pictures play an important role in clarifying complex concepts described in words. The second observation is that information is no Longer conveyed through one single mode but a multiplicity of modes. For example, it is rare to find the front page of a newspaper consisting of only words or only images. In fact, it is often a combination of both words and images. Furthermore, if one were to read the news from the internet, one would probably find that the information is presented through a combination of words, Images, sound and video. The paper is therefore premised on the argument that a multimodal framework for English Language assessment is essential in order (o make assessment more relevant to the real-world context. The first part of this paper begins with examining the make-up of typical mainstream secondary school English Language comprehension assessment papers. The second part then addresses some of the limitations of the assessment papers by proposing a multimodal framework which includes the types of questions we can raise from the inclusion of multimodal texts in assessment.